2009
DOI: 10.1038/bmt.2008.447
|View full text |Cite|
|
Sign up to set email alerts
|

Are there roles for observational database studies and structured quantification of expert opinion to answer therapy controversies in transplants?

Abstract: Approaches to determine whether one transplant-related therapy is better than another include: (1) using experimental data, such as those from randomized controlled trials (RCTs); (2) using observational data, such as those from observational databases (ODBs) and (3) using conclusions from the structured quantification of expert opinion based on a consideration of evidence from RCTs, ODBs and other sources. Large RCTs are widely and appropriately regarded as the gold standard of clinical investigation. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 70 publications
(65 reference statements)
0
19
0
Order By: Relevance
“…While the debate about the role of non-randomized studies and comparisons in guiding clinical practice is ongoing, 5,[45][46][47][48][49] empirical evidence seems to suggest that utmost caution is warranted: the list of examples in important public-health settings where the strong expectation of benefit from non-randomized studies has been replaced later by evidence of inefficacy or even harm is unfortunately long and telling (Table 1). In addition to the story of HDCT in breast cancer, it includes hormone replacement therapy for menopausal women (where instead of an expected 40-50% reduction in coronary diseases, 50 randomized data suggested that hormone replacement therapy carries increased risk of coronary disease 51 ), b carotene for lung cancer (where instead of reducing risk of lung cancer as suggested by observational studies (International Agency for Research of Cancer 52 ), randomized data showed increased increase in lung cancer incidence on the b carotene arm 53,54 ), vitamin E for coronary heart disease (where large, well-designed RCTs showed no reduction cardiovascular event rate, 55,56 contrary to the benefit reported in the observational studies 57,58 ) and arthroscopic knee surgery (that was reported to reduce pain in numerous uncontrolled studies 59 and is widely used in the treatment of osteoarthritis yet has not been shown to provide any benefit in randomized trials 59,60 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the debate about the role of non-randomized studies and comparisons in guiding clinical practice is ongoing, 5,[45][46][47][48][49] empirical evidence seems to suggest that utmost caution is warranted: the list of examples in important public-health settings where the strong expectation of benefit from non-randomized studies has been replaced later by evidence of inefficacy or even harm is unfortunately long and telling (Table 1). In addition to the story of HDCT in breast cancer, it includes hormone replacement therapy for menopausal women (where instead of an expected 40-50% reduction in coronary diseases, 50 randomized data suggested that hormone replacement therapy carries increased risk of coronary disease 51 ), b carotene for lung cancer (where instead of reducing risk of lung cancer as suggested by observational studies (International Agency for Research of Cancer 52 ), randomized data showed increased increase in lung cancer incidence on the b carotene arm 53,54 ), vitamin E for coronary heart disease (where large, well-designed RCTs showed no reduction cardiovascular event rate, 55,56 contrary to the benefit reported in the observational studies 57,58 ) and arthroscopic knee surgery (that was reported to reduce pain in numerous uncontrolled studies 59 and is widely used in the treatment of osteoarthritis yet has not been shown to provide any benefit in randomized trials 59,60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, randomized trial cannot simulate the diversity of subject-, disease- and transplant-related variable which a physician must consider when recommending a therapy or therapy-strategy. 7 …”
Section: Hla-haplotype-mismatched Transplantsmentioning
confidence: 99%
“…We tackled several of the issues in this paper in a previous report [53] with three additional co-authors (M. Eapen, B. Logan and M.J. Zhang) with a far greater knowledge of statistics than ours. The focus of that report was on the value of ODBs in addressing therapy questions in bone marrow and blood cell transplants.…”
Section: Acknowledgmentsmentioning
confidence: 99%